1999
DOI: 10.1046/j.1524-4725.1999.99070.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Primary Mucinous Carcinoma of the Eyelid Treated with Mohs Surgery

Abstract: Multiple lesions of mucinous carcinoma of the eyelid do not necessarily connote metastasis. Mohs microscopically controlled excision may be a suitable form of therapy for primary mucinous carcinoma of the eyelid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
0
23
1
Order By: Relevance
“…In our case the clear separation of some of the secondary lesions from the primary site makes it highly unlikely that local recurrence of the initial tumor was solely responsible for the development of the secondary lesions. Although multiple lesions do not necessarily indicate metastasis, and Bertagnoli et al 12 reported the occurrence of bilateral eyelid involvement in a single patient, the proximity of the multiple secondary lesions in our patient does suggest that these tumors may have arisen from intransit metastases. Multifocal in-transit metastases would explain the rapid development of numerous new lesions in the scalp of our patient.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In our case the clear separation of some of the secondary lesions from the primary site makes it highly unlikely that local recurrence of the initial tumor was solely responsible for the development of the secondary lesions. Although multiple lesions do not necessarily indicate metastasis, and Bertagnoli et al 12 reported the occurrence of bilateral eyelid involvement in a single patient, the proximity of the multiple secondary lesions in our patient does suggest that these tumors may have arisen from intransit metastases. Multifocal in-transit metastases would explain the rapid development of numerous new lesions in the scalp of our patient.…”
Section: Discussioncontrasting
confidence: 47%
“…3,4 Several recent reports have successfully utilized Mohs micrographic surgery to treat cutaneous mucinous carcinomas. [12][13][14] Mohs micrographic surgery appears to be a suitable and effective means of treatment since these tumors usually form contiguous masses. Tumor cells are also easily visualized in frozen sections utilizing the toluidine blue stain, and the Mohs technique ensures complete removal of the tumor, which routine surgical excisions may not accomplish.…”
Section: Discussionmentioning
confidence: 99%
“…39,49,56 Six previously reported cases of MEA treated with MMS pooled from the work of 5 different authors suggest no local recurrence after MMS with a follow-up time ranging from 2 to 5 years after MMS. 15,27,39,49,56 However, both patients in our series who were treated with MMS had local recurrence after MMS with clear margins. This suggests that local recurrence is still a concern despite the use of MMS.…”
mentioning
confidence: 63%
“…24 Mohs' micrographic surgery has been proposed as an effective treatment for many authors. 7,[45][46][47][48] The ability of magnetic resonance imaging to obtain images in multiple planes facilitates localization of the tumor and clarifies anatomic relationships, thus it can be helpful in the planning of surgical excision and staging the disease. 11 Fine-needle aspiration biopsy might also be useful in preoperative evaluation.…”
Section: Discussionmentioning
confidence: 99%